Chemical variables - stream from Mycklemossen, N-stream-1, 2018-05-29–2025-12-09 - Skogaryd Research Catchment (University of Gothenburg, 2026)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Skogaryd Research Catchment (2026). Chemical variables - stream from Mycklemossen, N-stream-1, 2018-05-29–2025-12-09 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/WmmdAvrnqJAkzfrMaYBlWlLF
Keywords: Skogaryd Research Catchment; Stream; Time instant; Time instant; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; pH; pH; Reference Water temperature for pH measurement; Reference Water temperature for pH measurement; Dissolved oxygen; Dissolved oxygen; Oxygen saturation; Oxygen saturation; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrate-N; Nitrate-N; Fluorine; Fluorine; Chlorine; Chlorine; Bromine; Bromine; Sulphate-S; Sulphate-S; Lithium; Lithium; Beryllium; Beryllium; Boron; Boron; Sodium; Sodium; Magnesium; Magnesium; Aluminium; Aluminium; Silicon; Silicon; Phosphorus; Phosphorus; Sulfur; Sulfur; Potassium; Potassium; Calcium; Calcium; Vanadium; Vanadium; Chromium; Chromium; Manganese; Manganese; Iron; Iron; Cobalt; Cobalt; Nickel; Nickel; Copper; Copper; Zinc; Zinc; Gallium; Gallium; Arsenic; Arsenic; Selenium; Selenium; Rubidium; Rubidium; Cadmium; Cadmium; Tellurium; Tellurium; Caesium; Caesium; Barium; Barium; Thallium; Thallium; Lead; Lead; Bismuth; Bismuth; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske